Activity of lipid peroxidation processes in pregnant women with chronic viral hepatitis - O. A. Nikitina (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Viral hepatitis is a traditionally complexglobal problem for humans and is still far from being solved. For the last decade the incidence of chronic viral hepatitis in the Russian Federation has grown by 2.2 times. Many researchers point out aggravating mutual influence of viral hepatitis and рregnancy. The severity and development prognosis of liver diseases are closely interlinked with the functional state of oxidant and antioxidant systems of hepatocytes. Objective is to estimate the intensity rate of liрid peroxidation in рregnant women with chronic viral hepatitis. The material for biochemical studies was blood plasma. The content of the substrates for Ирid peroxidation - compounds with isolated double bonds and the products of lipid peroxidation processes (diene conjugates, ketodienes and conjugated trienes, thiobarbituric acid active products] was determined with spektrofluorofotometre "SHIMADZU-1501" (Japan]. We used modern spectrophotometric and statistical methods. It was found that there is increased activity of Ирid oxidation in patients with chronic viral hepatitis. Blood plasma levels of intermediate and final products of Ирid peroxidation are significantly elevated in patients with chronic viral hepatitis, compared to the control groups. Increase in plasma peroxidation products indicates the рresence of oxidative stress in patients with viral hepatitis. Study of parameters of liрid peroxidation is an informative method for the correction of the disease in рregnant women with chronic viral hepatitis.